2008
DOI: 10.1111/j.1365-2958.2008.06201.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel regulatory protein governing biofilm formation in Bacillus subtilis

Abstract: SummaryProduction of an extracellular matrix is a hallmark of biofilm formation. In the spore-forming bacterium Bacillus subtilis, the matrix consists of an exopolysaccharide, which is specified by the epsA-O operon, and a secreted protein TasA, which is encoded by the yqxM-sipW-tasA operon. Past and present evidence establish that the epsA-O and yqxM-sipW-tasA operons are controlled by the repressor proteins SinR and AbrB. Here, we report the identification of a novel regulatory protein Slr that promotes tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
182
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(191 citation statements)
references
References 25 publications
9
182
0
Order By: Relevance
“…AbrB is a key transition-state regulator in Bacillus subtilis that affects the regulation of postexponential gene expression (Strauch and Hoch 1993;Phillips and Strauch 2002) and biofilm-forming gene expression (Chu et al 2008). cyAbrBs show rather low similarity to AbrB in amino acid sequence, but possess a bbabb structure at the C-terminal region that is characteristic of AbrB-like DNA-binding domains (Ishii and Hihara 2008).…”
Section: Introductionmentioning
confidence: 99%
“…AbrB is a key transition-state regulator in Bacillus subtilis that affects the regulation of postexponential gene expression (Strauch and Hoch 1993;Phillips and Strauch 2002) and biofilm-forming gene expression (Chu et al 2008). cyAbrBs show rather low similarity to AbrB in amino acid sequence, but possess a bbabb structure at the C-terminal region that is characteristic of AbrB-like DNA-binding domains (Ishii and Hihara 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm formation is governed by a regulatory circuit that involves three dedicated regulatory proteins: SinI, SinR, and SlrR Chu et al 2008;Kobayashi 2008). SinI is produced under the control of Spo0A, a global regulator of post-exponential-phase gene expression in B. subtilis (Gaur et al 1988;Sonenshein 2000;Piggot and Hilbert 2004;Fujita et al 2005;Chai et al 2008).…”
mentioning
confidence: 99%
“…SinR, in turn, binds to the promoters for matrix operons (yqxM and eps [exopolysaccharide]) and the gene for SlrR (slrR), blocking their transcription ( Fig. 1A; Branda et al 2006;Chu et al 2006Chu et al , 2008. SlrR is a hybrid protein, containing domains that are homologous to both the SinI anti-repressor and the SinR repressor .…”
mentioning
confidence: 99%
“…A survey of genes required for efficient biofilm formation in B. subtilis revealed that a med mutation confers a modest defect in biofilm colony morphology (9). Biofilms are composed of long chains of cells that are held together by an extracellular matrix consisting of protein and polysaccharide.…”
Section: Resultsmentioning
confidence: 99%